2018
DOI: 10.1097/mcg.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Rolling-out Screening Volume Affecting Compliance Rate and Waiting Time of FIT-based Colonoscopy

Abstract: The decrease in compliance rate and an increase in the WT with variation across geography and institution resulting from the increased volume of rolling-out FIT screening provide an insight into optimal resource allocation of clinical capacity for colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Delay of diagnostic colonoscopy may lead to increased likelihood of detecting a lesion at a more advanced or non‐curable stage. Rescheduling of or prolongation of waiting for colonoscopy is related with cancellation of colonoscopy, which may lead to more grave outcomes 25 . Our previous study has demonstrated that if people are not compliant to colonoscopy after positive FITs, then there was 60% higher risk of CRC death compared with those who were compliant 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Delay of diagnostic colonoscopy may lead to increased likelihood of detecting a lesion at a more advanced or non‐curable stage. Rescheduling of or prolongation of waiting for colonoscopy is related with cancellation of colonoscopy, which may lead to more grave outcomes 25 . Our previous study has demonstrated that if people are not compliant to colonoscopy after positive FITs, then there was 60% higher risk of CRC death compared with those who were compliant 26 .…”
Section: Discussionmentioning
confidence: 99%
“…People from low-socioeconomic backgrounds are more likely to receive care in underresourced healthcare settings such as community health centers or have limited or no access to colonoscopy. [104][105][106] Colonoscopy detects adenomas with high levels of sensitivity (50%-95%), as well as CRC (75%-95% specificity), 107 and allows for evaluation of detected lesions at the time of screening, without the need for an additional test. The infrequent screening interval might be advantageous to patients from underserved backgrounds who have frequent changes in contact information and/or insurance.…”
Section: Community Resources and Community-based Interventionsmentioning
confidence: 99%
“…Previous analyses of time-to-diagnosis primarily focused on FIT-positive patients, revealing that individuals who underwent colonoscopy more than 6 months after a FIT-positive result exhibited a notably elevated risk of advancedstage colorectal cancer. 29 The delay in diagnostic examination can be attributed to a variety of factors, including limited colonoscopy capacity following the expansion of FIT screenings after 2010, 30 lack of patient awareness about the significance of positive FIT results, limitations in healthcare services, extended waiting times that result in patient dropoff, and financial constraints that make examinations unaffordable for some individuals. 31 A recent study also assessed 14 However, it is important to emphasize that the study focused on individuals who had participated in screening previously, without distinguishing between different FIT results or evaluating whether follow-up examinations were conducted.…”
Section: Discussionmentioning
confidence: 99%